Percepções e práticas populares em saúde bucal - Caldas, Lucienne Venturim (2005)
The precarious conditions of the Brazilian adult s dental health reflect the exclusion and social inequalities established on the country and the effectiveness of the dental care and the public policies of dental health. For a long time isolated actions were executed, that were far apart from the reality of the people, which had very few impact in the epidemiological situation of the population and didn t increase the overall quality of life. Based on the pedagogical practices of health it s perceived that these activities are made based solely on the transmitted knowledge, without consideration of the values, creeds and conducts of the individuals and social groups related to their dental health. This fact determines the few changes on the people behavior and the absence of action for the development of the potentialities and capacities of the individuals toward the betterment of their health. Based on this point of view, this dissertation propose discover the values, creeds and attitudes related to the dental health of grown individuals, living in a district on the suburbs of Vitória ES, which will allow new perspectives in the way which these people signify and re-signify the health / disease process and, furthermore, stimulate an qualitative transformation on the methods and treatment in Dentistry. The adopted methodology has stressed the qualitative approach, characterized as case study, realized with ethnographic methods of data collection; which were semi-structured interview, direct observation and field notes. The analysis of the data involved four axis and was based on the theoretical referential of the medical anthropology, and others authors as Boltanski, Elias and Berger and Luckmann. It was concluded that the dental health was considered by the individuals an intrinsic condition of overall health, as constituting part of a healthy individual condition, integrated in a cultural and social context, which constitutes as a determinant factor on the development of the social relations, insertion on the work market and the demarcation of social asymmetries. From their personal biography and their lifelong relations with the social medium, these individuals create alternatives to deal with dental issues, set apart from the governmental subsided dental services. They also indicate that the access and quality of the service are the main conditions to be improved on the public oral health services.